Impact of electro-acupuncture on EAAT2 and NMDAR-2B expression in goats with visceral hypersensitivity - Adnan Hassan Tahir; Yi Ding; Juan Wan; Manoj Kumar Shah; Habibullah Janyaro; Xiao-Jing Li; Ming-Xing Ding (Heliyon)
Objective: This study evaluates the effect of electro-acupuncture (EA) on visceral hypersensitivity (VH) and the expression of N-methyl-D-aspartate receptor-2B (NMDAR-2B) and glutamate transporter EAAT2 in goats. Methods: Twenty-four goats were divided into four groups: saline, 2, 4, 6-Trinitrobenzenesulfonic acid (TNBS), TNBS + EA, and sham EA. EA was administered at Zusanli (ST36) with 60 Hz and 1–3 mA on specified days. Electromyography (EMG) recorded visceromotor response to colorectal distention (CRD). Spinal cords were collected for immunohistochemistry, western blotting, and RT-PCR. The ileum was examined histologically. Results: The repeated EA administration significantly attenuated VH (P < 0.05) in TNBS-treated goats without similar effects in the sham group. NMDAR-2B expression increased (P < 0.01), and EAAT2 expression decreased (P < 0.01) in the TNBS group compared to saline. EA increased the EAAT2 and decreased the NMDAR-2B expression (P < 0.01) compared to TNBS, with no change in the sham-EA group. Conclusion: EA may alleviate VH by upregulating EAAT2 and downregulating NMDAR-2B in the spinal cord of TNBS-treated goats, indicating its potential for treating chronic visceral pain in gastrointestinal disorders.